Strategi Penerapan Teknologi Informasi dan Komunikasi di Madrasah - Erwin Indrioko (LP2M STAI Darul Kamal NW Lombok Timur, 2019)
Technology has brought changes in all aspects of education where almost various problems of education cannot be separated from the existence of technology. The use of technology in madrasas is not a stranger in the era of globalization as it is today. The flow of technological development will move faster, this requires the madrasa to be able to adapt to the development of these technologies if they do not want to be abandoned by their customers. Some uses of information technology in the education process that can be applied in madrasas include; management information system, e-learning in learning, the use of information technology as a learning medium, for life skills education of students. Some of the main components of information and communication technology-based madrasas consist of at least: content and curriculum, learning processes, facilities and infrastructure in madrasas, competency of human resources in madrasas, madrasa administration systems. There are several steps in the development of information and communication technology including; set up computer laboratories, provide Free Wifi services, establish cooperation with relevant parties such as technology-based universities and the ministry of communication and information, establish madrasa technology workshops.